(untitled) (World Bulletin of Education and Learning, 2025)
This article provides a scientific analysis of the rapid development of neurotechnologies and their profound impact on human cognition, mental processes, and personal autonomy. It explores how technologies such as brain–computer interfaces and deep brain stimulation enable direct access to or modification of complex mental functions, including perception, memory, emotion, decision-making, and motor control. While these devices have the potential to expand human capabilities and enhance cognitive performance, the study highlights that they may simultaneously pose risks to fundamental human values such as personal identity, mental privacy, and individual agency. The discussion also addresses widespread misconceptions surrounding neurotechnologies, emerging concepts like brain-to-brain communication, and the possible consequences of future advancements aimed at cognitive enhancement. The scientific, ethical, and social dimensions of neurobiological approaches designed to elevate human cognitive abilities are examined, with particular attention to invasiveness, applicability, and mechanisms for integration into daily life. The article concludes with an assessment of future development prospects and research directions, offering recommendations for evaluating the impact of neurotechnologies on human functioning.